2010
DOI: 10.1136/hrt.2010.199042
|View full text |Cite
|
Sign up to set email alerts
|

Diesel exhaust inhalation does not affect heart rhythm or heart rate variability

Abstract: Brief exposure to dilute diesel exhaust does not alter heart rhythm or heart rate variability in healthy volunteers or well-treated patients with stable coronary heart disease. Autonomic dysfunction does not appear to be a dominant mechanism that can explain the observed excess in cardiovascular events following exposure to combustion-derived air pollution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
2
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 35 publications
4
47
2
1
Order By: Relevance
“…Hence, the association between HRV and PM exposure is not only seen in susceptible subgroups. Contrary to our meta-analysis, a recent experimental study9 found no effects of dilute diesel exhaust inhalation for 1 h on heart rhythm and HRV in healthy volunteers or in an ‘at-risk’ population of patients with stable coronary heart disease. Explanations for the discrepancy between these epidemiological data and negative results in controlled conditions may include too short exposure and difference pollution mixture.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Hence, the association between HRV and PM exposure is not only seen in susceptible subgroups. Contrary to our meta-analysis, a recent experimental study9 found no effects of dilute diesel exhaust inhalation for 1 h on heart rhythm and HRV in healthy volunteers or in an ‘at-risk’ population of patients with stable coronary heart disease. Explanations for the discrepancy between these epidemiological data and negative results in controlled conditions may include too short exposure and difference pollution mixture.…”
Section: Discussioncontrasting
confidence: 99%
“…Reduced HRV has been associated with an increased risk of myocardial infarction among the population7 and has been considered as a predictor of increased risk of mortality in patients with heart failure 8. The importance of this pathway is still under debate 9 10. Here we determine whether all the available observational data up to February 2012 support a positive association and how strong such a relationship between HRV and particulate air pollution may be.…”
Section: Introductionmentioning
confidence: 89%
“…Mills et al (2007) reported that exposure of men with previous myocardial infarction (MI) to DE at 300 mg PM/m 3 increased exercise-induced depression of the S-T segment of the electrocardiogram. However, the same group (Mills et al, 2011) did not reproduce the finding in a later study of both normal subjects and men with previous MI exposed to the same concentration of DE. There are no reports of the effects of GE, WS or a mixture similar to CE on heart rate and rhythm of humans or animals.…”
Section: Heart Rate and Rhythm In Shr Ratscontrasting
confidence: 59%
“…Changes in heart rate variability have been studied. A link between such changes and pulmonary inflammation has been suggested (McQueen et al 2007, Pieters et al 2012, Mills et al 2010Schneider et al 2010;Robertson et al 2014;Chuang et al 2007;Rhoden et al 2005).…”
Section: Evidence Speculations and Hypothesesmentioning
confidence: 98%